Synthesis of Polymer-Derived Carbon for Ibuprofen Removal from Simulated Wastewater - Mutia, Aulia Septiani; Prasetyo, Imam; Ariyanto, Teguh (Trans Tech Publications, 2022)
Ibuprofen is a nonsteroidal anti-inflammatory drug classified as one of the emerging contaminants from the pharmaceutical groups. Ibuprofen detected in the environment indicates that wastewater treatment facilities have a limited ability to remove this substance. Residual ibuprofen that accumulates continuously can harm ecosystems in the waters and indirectly affects human health. Adsorption using porous material is a method that can reduce the amount of ibuprofen in wastewater. This research synthesized porous carbon by pyrolysis of phenolic polymer. The resulting material was then characterized using an N2-sorption analyzer, SEM, and XRD. After being characterized, the material was used to adsorb ibuprofen at various concentrations. The SEM characterization showed that carbon had voids or channels for adsorbing ibuprofen molecules. The N2-sorption analyzer delivered that the polymer-derived carbon has a specific surface area of about 594 m2 g-1 . Based on the adsorption test result, the porous carbon could adsorb the ibuprofen molecules in the simulated wastewater well and followed the Freundlich equilibrium model. © 2022 Trans Tech Publications Ltd, Switzerland.